2021
DOI: 10.3390/catal11101236
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for the Immobilization of Eversa® Transform 2.0 Lipase and Application for Phospholipid Synthesis

Abstract: Eversa® Transform 2.0 lipase (ET2) is a recent lipase formulation derived from the Thermomyces lanuginosus lipase cultivated on Aspergillus oryzae and specially designed for biodiesel production. Since it has not been available for a long time, research on the efficiency of this enzyme in other applications remains unexplored. Moreover, even though it has been launched as a free enzyme, its immobilization may extend the scope of ET2 applications. This work explored ET2 immobilization on octadecyl methacrylate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…It has been reported that ET 2.0 has the greatest catalytic activity at temperatures of 25 • C−40 • C. However, several reports employing immobilized ET 2.0 as the biocatalyst for different types of reactions have found that the immobilized lipase display higher optimal temperatures (45 • C−65 • C) than their free counterparts (Facin et al, 2021;Lee et al, 2019;Oh et al, 2022). These results suggest that the immobilization of ET 2.0 on support materials might enhance the thermostability of the lipase.…”
Section: Effect Of Temperaturementioning
confidence: 99%
“…It has been reported that ET 2.0 has the greatest catalytic activity at temperatures of 25 • C−40 • C. However, several reports employing immobilized ET 2.0 as the biocatalyst for different types of reactions have found that the immobilized lipase display higher optimal temperatures (45 • C−65 • C) than their free counterparts (Facin et al, 2021;Lee et al, 2019;Oh et al, 2022). These results suggest that the immobilization of ET 2.0 on support materials might enhance the thermostability of the lipase.…”
Section: Effect Of Temperaturementioning
confidence: 99%